TAKLIM MUTA'ALIM: MENANAMKAN ADAB DAN KEBERKAHAN DALAM PENDIDIKAN - Fatoni, Imam (Institut Islam Mamba'ul 'Ulum Surakarta, 2025)
Education in Islam does not only emphasize the intellectual aspect, but also instills the values of manners and the blessings of knowledge.the values of manners and the blessing of knowledge. The book Ta'lim al-Muta'allim by Sheikh Az-Zarnuji is one of the classical references that discusses the correct learning method, the importance of adab towards the teacher, and how knowledge can bring blessings. learning methods, the importance of adab towards teachers, and how knowledge can bring blessings to individuals and society. blessings for individuals and society. This research aims to examine the concept of education in Ta'lim al-Muta'allim and its relevance in the modern education system. Modern education system. By using the library research method, this research analyzes the principles of education in Ta'lim al-Muta'allim research method, this study analyzes the principles of Islamic education as stated in the book and its implications for learning. Principles contained in the book as well as its implications for current learning. The results show that the values taught in Ta'lim al-Muta'allim, such as sincerity in the pursuit of knowledge, respect for teachers, and the practice of knowledge for the sake of learning today. Respect for teachers, and the practice of knowledge for the benefit of society, are still very relevant in shaping the character of character of students who are not only academically intelligent but also have high morality. Also have high morality. The concept of adab and blessing in education can be a solution to the challenges of contemporary education, especially in building a generation that is knowledgeable and noble.